Investigating South Africa's protection of refugee womxn: Refugee womxn's access to housing, inclusion into the labour market and protection from gender-based violence - Louw, Danielle (Department of Public Law, 2021)
This paper investigates the integration experience of refugee womxn in South Africa. It focuses on the areas of access to housing, employment and protection from gender-based violence. Through a human rights approach, influenced by intersectional feminist theory, it analyses the international normative and South African domestic framework and discusses its gaps and challenges. Thereafter, an overview of the experience of refugee womxn's access to housing, employment and protection from gender-based violence internationally and in South Africa is presented. Lastly, recommendations are made to the South African state suggesting reform in law, policy and practice.